Perbandingan Efektivitas Pencampuran Ekstrak Daun Sirih (Piper Betle) dan Daun Bengkuang (Pachyrhizus Erosus) dengan Abate Terhadap Mortalitas Larva Aedes Aegypti - Marjan Wahyuni; Rusdi Rusdi (Jurnal Ilmu Kesehatan, 2017)
Dengue Haemorrhagic Fever (DHF) is a disease that is still a major problem in Indonesia. Until now there is no cure or vaccine to combat dengue, so the only way is to break the chain of transmission of mosquito Aedes aegypti is the prevention or control of disease vectors. This study aims to determine the Efficiency of Mixed Leaf Extract (Pipper Betle) and Leaf Yam Extract with Temephos On Mortality of Aedes aegypti. This research is experimental and research will be conducted in the laboratory of environmental health. The number of treatment in this study was 3 treatment with different doses of 0.5 mg / l ; 1.0 mg / l ; 1.5 g / l ; 2m g / l and 1 control (0 mg / liter) were treated in the larvae mosquitoes. The results showed that the air temperature at the study site averaged 27oC, the air humidity between 78-79%, the water temperature that became the Aedes aegypti breeding 26-27oC, the average pH 6.8-7. The results showed that the leaf extract beta and bengkuang leaves at a dose of 2.0 mg / l for 24 hours were able to kill Aedes aegypti larvae of 96.6%, while abates with a dose of 2.0 mg / l for 24 hours were able to kill Aedes aegypti larva by 70%. After statistical analysis with Independent t-test showed that betel leaf extract and bengkuang leaf gave a significant effect on the mortality of Aedes aegypti larvae. So it can be concluded that there is a significant effectiveness difference between bengkuang leaf extract (Pachyrrhyzus erosus) and betel leaf (Piper betle) with abate to mortality of Aedes aegypti larvae. for the mortality of Aedes aegypti larvae both in terms of average mortality (p = 0.003) and in terms of mean duration (p = 0,000) and there was a significant relationship (p = 0,000) between giving both larvacides to Aedes aegypti larvae mortality. This research suggests to the public to use organic larvacides and to reduce the use of abate.